2013
DOI: 10.1093/europace/eut161
|View full text |Cite
|
Sign up to set email alerts
|

A prospective evaluation of haemodynamics, functional status, and quality of life after radiofrequency catheter ablation of long-standing persistent atrial fibrillation

Abstract: Ablation of long-standing persistent atrial fibrillation was associated with significant recovery of haemodynamics and exercise capacity that projected onto the long-term improvement in quality of life.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
31
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(31 citation statements)
references
References 30 publications
0
31
0
Order By: Relevance
“…In addition, the extent of atrial ablation, which is often required to terminate persistent AF, has been repeatedly questioned, although recent studies (including reports from this population) showed that benefits from restored SR in terms of hemodynamic, functional, and quality-of life-improvement outweigh possible deleterious effects of extensive persistent AF/LSPAF ablation. 10,[13][14][15] The major findings of this study are as follows. (1) Nonrestoration of SR by ablation at the initial procedure is the dominant factor associated not only with clinical failure of the primary procedure but also with AF/AT recurrence after subsequent repeat procedure(s).…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…In addition, the extent of atrial ablation, which is often required to terminate persistent AF, has been repeatedly questioned, although recent studies (including reports from this population) showed that benefits from restored SR in terms of hemodynamic, functional, and quality-of life-improvement outweigh possible deleterious effects of extensive persistent AF/LSPAF ablation. 10,[13][14][15] The major findings of this study are as follows. (1) Nonrestoration of SR by ablation at the initial procedure is the dominant factor associated not only with clinical failure of the primary procedure but also with AF/AT recurrence after subsequent repeat procedure(s).…”
Section: Discussionmentioning
confidence: 85%
“…10 In brief, point-by-point ablation with an irrigatedtip catheter (NaviStar ThermoCool, Biosense Webster, Diamond Bar, CA) navigated in preacquired 3-dimensional electroanatomic maps (CARTO, Biosense Webster) of the LA and right atrium (RA) was performed off warfarin, with class I or III antiarrhythmic drugs (AADs) discontinued except for amiodarone, target activated clotting time of 300-400 seconds, irrigation at 20 mL/min, temperature 421C, and power limit of 35 W (20-25 W inside the coronary sinus [CS]). …”
Section: Preablation Examinationmentioning
confidence: 99%
“…Finally, 18 studies that met the inclusion criteria were included in our meta-analysis. Among them, 10 studies 8,[12][13][14][15][16][17][18][19][20] evaluated the association between baseline BNP levels and AF recurrence after catheter ablation while the 8 other studies [21][22][23][24][25][26][27][28] investigated the potential role of NT-pro BNP. Study characteristics: The demographic and clinical properties of eligible studies are presented in Table I and Table II, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…Fifteen studies [7][8][9][10][11][12][13][14][15][16][17][18][19][20][21] meeting the prespecified inclusion criteria, and 11 long-term (≥2 years) AFCA studies, [22][23][24][25][26][27][28][29][30][31][32] for which the corresponding author was contacted and agreed to participate, were eventually included. First author, study design, publication date, and main characteristics of each included study are reported in Table 1 in the Data Supplement (Material in the Data Supplement).…”
Section: Resultsmentioning
confidence: 99%